Alokasi Dana Desa Tolongano Kecamatan Banawa Selatan Kabupaten Donggala Provinsi Sulawesi Tengah - Fitriani Abdullah; Ihlal Langunja (Formosa Journal of Sustainable Research, 2022)
This study aims to determine and describe the Implementation of the Village Fund Allocation Policy of Helpano Village, South Banawa District, Donggala Regency, Central Sulawesi Province. The usefulness of this research is Theoretical and Practical. The Literature Review explains the concept of Administration, Public Administration, Public Policy, Policy Implementation and Village Fund Allocation. The flow of thought by the theory of Van Meter and Van Horn which includes the Standards and Objectives, Resources, Characteristics or Nature of the Implementing Agency, Inter-Organizational Communication, Implementor Disposition and the Socio-Economic and critical Environment. Research with qualitative methods, research location in the village of Helpano, South Banawa sub-district, research time for three months, informants are elements related to the allocation of village funds, namely 5 (five) people The definition of the concept is related to the implementation model of the policy. Types of qualitative data, and data sources are secondary data and primary data. The discussion explains the results of interviews and the results of analysis and theory in gambling. The researcher concludes that its implementation in the field of implementing the function has not fully gone well, Lack of understanding of the community about the Village Fund Allocation program so that there is a need for socialization and transparency of the use of Village Fund Allocation funds from the village government then accountability for the use of Village Fund Allocation by village financial managers. Accountability for the use of Village Fund Allocations is a form of consequence for the use of public funds entrusted to the village government.